Young Chinese WeChat Users' Brand Following Behavior - Shin, Wonsun; Huo, Yan (UI Scholars Hub, 2019)
Brand-following of consumers on social media constitutes an important return on investment (ROI) index in digital marketing. However, little is known to date regarding brand-following behaviors of young Chinese social media users on Chinese social media platforms, in addition to the factors associated with them. In this study, our in-depth interviews with 20 emerging adults who followed brands through WeChat indicated that materialistic values, brand-related peer communication, and parents’ opinions regarding different product categories impact the brand-following behaviors of young consumers. The interviews also demonstrated that young people’s brand-following affected their intentions to post brand-related messages that were pertinent to luxury brands. However, their purchase intentions were limited to the most affordable items from those luxury brands. In addition, they were less likely to repost brand information created and provided by marketers. Theoretical and practical implications are discussed herein, and suggestions for future research provided.